If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = x + 8ln(3x) Multiply f * x fx = x + 8ln(3x) Remove parenthesis around (3x) fx = x + 8ln * 3x Reorder the terms for easier multiplication: fx = x + 8 * 3ln * x Multiply 8 * 3 fx = x + 24ln * x Multiply ln * x fx = x + 24lnx Reorder the terms: fx = 24lnx + x Solving fx = 24lnx + x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 24ln + 1 Simplifying f = 24ln + 1 Reorder the terms: f = 1 + 24ln
| b^2-b-20=20 | | -7n=70 | | 5xy^2-3x+2y^2+7x+13xy^2= | | 97-9x=-47 | | 10x^2+6x=4 | | 11x+39=x-61 | | (8)n=48 | | 8k-5k=2-6+6k+1 | | a-18=-15 | | 64-8k=72 | | 4x(3x-7)-19x^2= | | (6)m=45 | | -14=n-1 | | 6d+11=3d+47 | | -16+3k=-28 | | 7x+7=8x+31 | | 43=3c | | 10=p+10 | | X^3-6x^2=x-30 | | -21=a-1 | | 2x+78=4x+24 | | .75y+8=23 | | 7(3x+8)=107 | | 3(x)+4=10 | | 3(y+6)fory=2 | | .4x-2+.5x=-1.28 | | 69=18-29 | | f(x)=(x^2)+11x | | -4(-6x-1)-4x=1 | | 8x^7+12x^4+24x^3= | | 2y-10=2 | | -9.2(3-x)=55.2 |